PENGARUH MOTIVASI EKSTRINSIK TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SMP - Mariwati, Kartika; Saija, Louise M (Jurnal Padegogik, 2024)
The main purpose of this study is to determine whether there is an effect of extrinsic motivation towards the mathematical understanding ability of junior high school students who learn using the STAD cooperative learning model. Extrinsic motivation is motivation that comes from outside the individual, and mathematical understanding ability shows students' ability to absorb, remember, and use formulas and theorems in solving mathematical problems, while the STAD cooperative learning model utilizes cooperation between students to achieve learning goals. The method used is a quantitative method with a descriptive correlational research design. The sample was selected in classes VII-C and VII-D at SMPN 1 Parongpong, West Java. This research uses test instruments for students' mathematical understanding abilities and extrinsic motivation questionnaires. The results showed that: 1) The indicators of extrinsic motivation of junior high school students have moderate and high categories, and the use of the STAD-type cooperative learning model can increase the extrinsic motivation of junior high school students. 2) Most students (sixty-six percents) have moderate mathematical understanding ability, twenty four percents high, and ten percents low. These results indicate that junior high school students' mathematical understanding abilities can still be improved.  3) The extrinsic motivation of Junior High School Students who learn using STAD cooperative learning mode affects their mathematical understanding ability.